Morphokinetics and embryo aneuploidy: has time come or not yet? - Montag, Markus (Reproductive biomedicine online, 2013)
Morphokinetic analysis of early human embryos in combination with trophectoderm biopsy and chromosomal enumeration by array technology has been shown to identify embryos with single and/or multiple aneuploidies. In a time-lapse imaging study, aneuploid embryos showed a delayed initiation of blastocyst formation and also reached the full blastocyst stage later compared with euploid embryos. Based on these findings, a model for a risk factor classification for aneuploidy of human embryos has been established. However, time values that allow differentiation between different risk classes have to be considered carefully as timings that are prognostic for one clinic may not apply directly to another clinic. Thus, risk models may need to be verified in specific IVF settings. Further studies are needed to verify that time-lapse imaging does allow subselection of embryos with a high aneuploidy risk and thus does hold the chance to restrict invasive biopsy procedures to those embryos where there is uncertainty regarding the chromosomal status.